Motor‐induced oscillations in choice response performance. (30th August 2022) - Pomper, Ulrich; Ansorge, Ulrich
Abstract: Recently, numerous studies have revealed 4–12 Hz fluctuations of behavioral performance in a multitude of tasks. The majority has utilized stimuli near detection threshold and observed related fluctuations in hit‐rates, attributing these to perceptual or attentional processes. As neural oscillations in the 8–20 Hz range also feature prominently in cortical motor areas, they might cause fluctuations in the ability to induce responses, independent of attentional capabilities. Additionally, different effectors (e.g., the left versus right hand) might be cyclically prioritized in an alternating fashion, similar to the attentional sampling of distinct locations, objects, or memory templates. Here, we investigated these questions via a behavioral dense‐sampling approach. Twenty‐six participants performed a simple visual discrimination task using highly salient stimuli. We varied the interval between each motor response and the subsequent target from 330 to 1040 ms, and analyzed performance as a function of this interval. Our data show significant fluctuations of both RTs and sensitivity between 12.5 and 25 Hz, but no evidence for an alternating prioritization of left‐ versus right‐hand responses. While our results suggest an impact of motor‐related signals on performance oscillations, they might additionally be influenced by perceptual processes earlier in the processing hierarchy. In summary, we demonstrate that behavioral oscillations generalize to situations involving highly salient stimuli, closer to everyday life. Moreover, our work adds to the literature by showing fluctuations at a high speed, which might be a consequence of both low task difficulty and the involvement of sensorimotor rhythms. Abstract : Numerous studies have revealed 4‐12 Hz fluctuations in performance, using stimuli close to detection threshold. Here we report oscillations in response times and sensitivity at 12‐25 Hz, employing a simple task and highly salient stimuli. We conclude that the phenomenon can be generalized to situations closer to everyday life, while the higher frequency likely reflects both reduced task difficulty and the involvement of sensorimotor neural oscillations.